Study of the attitude of students towards new technological contexts and neuroscience progress - Llamas Salguero, Fátima; Martín Lobo, Pilar; Pradas Montilla, Silvia; Gil Nájera, Marta (Ingeniería Solidaria, 2017)
Introduction: Technology and Neuroscience have formed a strong collaboration to improve education. The effective use of information and communication technologies (ict) in education practice requires that both students and teachers maintain a positive attitude towards these technologies, and develop their use in educational contexts to update teaching methodologies based on educational neuroscience and neuropsychology. Thus, the use of ict requires a positive attitude when using these tools during the teaching-learning process, as a starting point to improve the quality of the process. The article was written in the year 2016 in the faculty of Education of the Universidad Internancional de la Rioja.Methodology: The aim of this study is to analyze the student´s attitudes towards the use of new technologies in primary school classrooms. We designed a questionnaire and gave it to 1,770 students aged 11 and 12 years from 50 ceip (Infant and Primary schools).Results: In general, the results show that whilst students of 11 and 12 years do not show a rejection of the use of ict, a low percentage demonstrate that they would prefer to use them in a group.Conclusions: An adequate use of ict in the classroom would depend on the predisposition of the students, and the knowledge of the technologies and their use by teachers and students. Therefore, it is recommended for ict to be implemented in the classroom in order to improve the teaching-learning process and to incorporate new methodologies from neuroscience research.
Keywords: ICT; innovation; learning; neuropsychology; student; teacher